BANKERS’ PERSPECTIVE ON SOCIAL MEDIA BANKING: A STUDY WITH SPECIAL REFERENCE TO SELECT INDIAN BANKS - Ramasamy, Mani; Subbiah, Janakiraman; Bordoloi, Dhrubajyoti; Ramalingam, Perumalraja (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Social Media Banking (SMB) is an electronic banking channel enabling users to perform their banking services and operations through social media. Most Indian banks use social media for advertisement, customer relations, and marketing communications of products and services, but only a few banks offer services related to social media banking. The main aim of this paper is to study the Bankers' perspective on Social Media Banking services provided by banks in India and the effect of demographic profiles. Primary data was collected through a structured questionnaire to achieve the above goal. The study considered selective public and private sector banks, and the significant variables were social media adoption in banks, benefits, and challenges of SMB. The researcher adopted a simple random sampling method to collect the data from 402 bank bankers who offer social media banking-related services to their customers, and the statistical tools used to attain the objectives of this study are the Independent sample t-test and ANOVA test. The study results from banking professionals whose banks offered SMB services showed a significant effect of demographic variables on social media adoption in banks and the benefits and challenges of SMB. The study's findings provide regulators and banks with insight into the benefits and challenges of social media banking, enabling them to implement a generalized framework and guidelines on social media banking. The researcher suggests to the banks that the benefits and challenges of social media banking pave the way to developing efficient and flawless models for their customers. At last, the study encourages customers to move towards social media for their relationship with banks and real-time grievance redressal.JEL Classification Codes: M150, G21, L86, O360